Alternative Certification Programs in K-12 Schools: The Experiences of Diverse Teachers - Uddin, Muhammad Sharif (Journal of Education and Training, 2024)
Through individual interviews and focus groups, this qualitative phenomenological study explored 11 conditionally licensed teachers’ experiences in earning their full teaching license in a Mid-Atlantic state in the United States. Data were analyzed using a thematic analysis method. The findings of this study showed that the conditionally licensed teachers were career changers from diverse ethnic identities, and they mainly struggled with classroom management. The study also found that they had little support and information regarding the certification process, and their work-life-study balance was challenging. This study suggests that schools, school districts, and the university develop strong partnerships to provide appropriate support to these teachers to make them licensed and effective classroom teachers in order to meet the needs of the national teacher shortage.